2009
DOI: 10.1093/ntr/ntp014
|View full text |Cite
|
Sign up to set email alerts
|

Changing age-specific patterns of cigarette consumption in the United States, 1992–2002: Association with smoke-free homes and state-level tobacco control activity

Abstract: That this reduction is offset by an increase in light and intermittent smoking in young adults suggests the effectiveness of tobacco industry marketing and needs further research. IntroductionIn the early 1990s, the key smoking questions in national surveys in the United States were changed to better capture the cross-sectional prevalence of light or intermittent smoking behavior ( Giovino et al., 1994 ). Although cigarette consumption levels below 5 cigarettes/day (CPD) have been labeled as insuffi cient for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 25 publications
(32 reference statements)
8
74
1
Order By: Relevance
“…This finding follows a similar trend among young people in the general population (Pierce et al 2009), and university students in the USA (Moran et al 2004). Occasional smokers were also found to be heavier drinkers than daily smokers.…”
Section: Discussionsupporting
confidence: 82%
“…This finding follows a similar trend among young people in the general population (Pierce et al 2009), and university students in the USA (Moran et al 2004). Occasional smokers were also found to be heavier drinkers than daily smokers.…”
Section: Discussionsupporting
confidence: 82%
“…Individuals on these smoking trajectories comprised 28% of the sample (12% early, 16% late) compared to 60% who remained non-smokers over time, 6% who experimented with smoking in adolescence and reported no smoking after age 20, and 5% whose smoking progressed rapidly from middle to late adolescence, peaked around age 20-21, then declined to zero after age 25. Consistent with evidence on the increase in light or intermittent smoking among young adults (Pierce et al 2009) and smoking initiation after age 18 (Foldes et al 2010;Thompson et al 2017), stable, lower-level smoking was added as a distinct trajectory in two 2008 studies (Brook et al 2008;Costello et al 2008). In a study from 1975 to 2002 of participants aged 14-32 years, Brook et al found that Boccasional smokers^escalated their smoking between ages 16 and 22, maintaining a pattern of non-daily smoking through their thirties (approximately 10% of the sample).…”
Section: Young Adults and Tobacco Usesupporting
confidence: 80%
“…Studies have shown that smoking in adolescents is related to a social context more permissive of smoking ( Buller et al, 2003 ) and living with smokers ( Robinson et al, 2006 ). In one recent study ( Pierce et al, 2009 ), a smoke-free home signifi cantly increased the odds of being a light or intermittent smoker. Additionally, smoke-free environments (e.g., home, workplace) increase the likelihood of abstinence ( Fiore et al, 2008 ).…”
Section: Discussionmentioning
confidence: 98%
“…Despite a decrease in smoking among middle-aged and older adults, young adult smoking prevalence declines are smaller, and reductions in moderate to heavy smoking have been accompanied by an increase in prevalence of light and intermittent smoking ( Pierce, White, & Messer, 2009 ). One group of young adults who demonstrate high rates of smoking are individuals serving in the military ( Bray et al, 2006 ;Nelson & Pederson, 2008 ).…”
Section: Introductionmentioning
confidence: 99%